Internalizing Digital Technology in Islamic Education - Muslim, Muslim (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study analyzes the integration of digital technology into Islamic education to address moral challenges in the digital era. Employing a literature review with content analysis, this research evaluates primary and secondary sources, including academic journals, government reports, and authoritative references. The findings reveal that digital technology, such as augmented reality (AR) and artificial intelligence (AI), offers transformative opportunities for Islamic education by enhancing learning engagement, accessibility, and interactivity. However, the integration of these tools poses risks, including diminished moral values, reduced religious literacy, and dependency on technology, which require strategic interventions. This study emphasizes the importance of aligning technological advancements with Islamic principles to uphold spiritual and ethical integrity while fostering innovation in teaching and learning methods. Recommendations include the development of technology-based curricula that harmonize religious and scientific knowledge, training programs for educators to effectively utilize digital tools, and policies to mitigate negative impacts on student character and behavior. Furthermore, the application of AR in Islamic studies and AI-based personalized learning provides immersive and meaningful educational experiences, fostering intellectual and moral growth. This research contributes insights into leveraging digital tools to adapt Islamic education to the demands of the digital age while maintaining its foundational values. Future studies are encouraged to explore the long-term impacts of technology integration across various educational levels to ensure sustainable and effective Islamic education reform.